Pembelajaran Memahami Informasi Dengan Mendengarkan Berita Di Kelas Xi Siswa Madrasah Aliyah Negeri 1 Boyolali - Suyanto, Suyanto, Prof. Dr. Markhamah, M.Hum, Dr. Yakub Nasucha, M,Hum (2014)
This study is a qualitative descriptive that takes sample at Madrasah Aliyah Negeri 1 Boyolali. The data are words and actions. The data source are from speakers, the Indonesian teaching learning activities, and documents. The speakers are derived from the Indonesian language teacher and her students. The teaching learning activities took place in the second semester of grade XI majoring in science in 2012/2013 academic year. The documents are derived from all documents relating to the written learning activities. The collecting data techniques used are interview, discussion, and assignments. Research findings in the field are; Learning procedure in listening the news at grade XI of Madrasah Aliyah Negeri 1 Boyolali. The type of the study is a case- study. The data source is derived from: (1) Facts or events, (2) the speakers' ideas, and documentation. The collecting data techniques used are interview, observation, and analyzing the documents. Examining the validity of the data uses the triangulation of data source and method. The technique of analyzing data used is the Interactive analysis mode. The result of the research and its criticism involve: (1) the result of the study expresses: the teaching learning handled by the teacher, the teaching material, the method of the teaching learning activities, and the students; (2) The discussion on: (a) the activities of teaching learning in listening news; (b) the causes of the teaching learning in comprehending news does not run maximally. Based on the data analysis, it can be concluded that: 1. The teaching learning activities in comprehending the news can be carried out as follows: (a) the teacher did not do pre-listening activities and does not lead her students to have a good discussion; (b) making groups of discussion is only based on the gender; male and female; (c) recording the material interferences the students while they have a listening class; (d) the students do not communicate to each other smoothly and interactively. The causes of the problem in teaching learning activities dealing in listening are: (a) the teacher does not do pre-listening activities and does not motivate them to have a good discussion, because the teacher is used to teaching the material directly; (b) making groups of discussion is only based on the gender; because she does not do it seriously; (c) the recording material is derived from you-tube, but the equipment of the sound-system is inadequate and the classroom is by the main road that is veryobstreperous; (d) the students does not communicate smoothly and interactively, because they are not used to communicate formally.